1997
DOI: 10.1109/95.623029
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion strength and microstructural evaluation in electroless Ni-P metallized AlN substrate

Abstract: The adhesion strength of the electroless Ni (EN)plated AlN substrates is studied through investigation of the microstructural morphologies at the AlN-EN interfaces. Etching sites around the Al-Y-O compounds on the etched AlN substrate provide the anchor acceptors for interlocking the EN film to achieve a high adhesion strength. Separation of the EN film from the AlN substrate under the action of force leaves the fracture cracks propagating along the AlN/EN interface, cutting through the anchors and making the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Yoshiki et al [11] reported an electroless copper layer on ceramic substrate with the adhesion strength of greater than 25 MPa by using an intermediate layer of ZnO thin film, which was prepared by spray pyrolysis. Although high temperature favor the formation of strong chemical bonding between the ZnO film and the substrate, the residual stress needs to be reduced by annealing for as long as 2 h. Chung-Daw and Jenq-Gong [12] etched the ceramic substrate using a 4 wt.% NaOH solution for 3 h to obtain a rough surface, and an adhesion strength of 13.7 MPa was achieved. However, the inefficient pretreatments are likely to limit the practical use of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshiki et al [11] reported an electroless copper layer on ceramic substrate with the adhesion strength of greater than 25 MPa by using an intermediate layer of ZnO thin film, which was prepared by spray pyrolysis. Although high temperature favor the formation of strong chemical bonding between the ZnO film and the substrate, the residual stress needs to be reduced by annealing for as long as 2 h. Chung-Daw and Jenq-Gong [12] etched the ceramic substrate using a 4 wt.% NaOH solution for 3 h to obtain a rough surface, and an adhesion strength of 13.7 MPa was achieved. However, the inefficient pretreatments are likely to limit the practical use of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Roughening their surfaces and then using electroless deposition was a common approach. 27,[33][34][35][36][37][38][39][40][41] Surface metallization, mask design, photoresistant coating, exposure, development, and then pattern etching are the standard operation process (SOP) for RDL formation on the ceramic substrates. The SOP takes a long time and is expensive, even high risk, because the process flow is long, the palladium used as the catalyst of the electroless deposition is expensive, and after baking the copper electroless deposition layer, copper blister may be formed on the substrates.…”
mentioning
confidence: 99%